ENVIRONMENTAL AUDIT: AN COMPANY’S OBLIGATION OR NECESSITY - Moh. Faisol; Nur Fadjrih Asyik; Wahidahwati (RISTANSI: Riset Akuntansi, 2026)
This article aims to explore the position of environmental auditing from the perspective of a corporate obligation or need. The method used is a conceptual study based on an analysis of the underlying theory of environmental audits in companies. The results of the analysis and study stated that (1) environmental audits are seen as a corporate obligation that must be fulfilled both legally and morally; and (2) environmental audits are a need for the company's "strategic role" in the context of sustainability for competitive advantage. However, making environmental audits a necessity is more profitable. Because companies do not just conduct environmental audits symbolically but make them a necessity that enables them to build sustainable competitive advantages through efficiency, innovation, and a positive image. This study implies that symbolic activities carried out by companies will not provide value or competitiveness in the long term but will only serve to drop obligations.